Reaction of Carbidopa with cis-[Cr(C2O4)2(H2O)2]− in Aqueous Medium: A Kinetic, Mechanistic and Antiparkinsonian Study of the Product Complex - Rout, Sudhanshu Sekhar; Kar, Durga Madhab; Si, Sudam Chandra; Patnaik, Ajaya Kumar; Mohanty, Prakash (Asian Journal of Chemistry, 2020)
For the treatment of Parkinson′s disease, the second most common neurodegenerative disorder, requires a combination of levodopa with a peripheral decarboxylase inhibitor, such as carbidopa which provides a symptomatic relief to patients. Reaction of carbidopa with cis-[Cr(C2O4)2(H2O)2]– has been carried out in aqueous medium over the range 35 ≤ t ≤ 50 ºC, 4.0 ≤ pH ≤ 6.0 , 3.75 × 10-3 mol dm-3 ≤ [carbidopa] ≤ 9.38 × 10-3 mol dm-3, I (KNO3) = 0.1 mol dm-3. There is outersphere association between cis-[Cr(C2O4)2(H2O)2]– and conjugate base of carbidopa followed by first chelation. The characterization of the product was performed by using NMR and infrared spectroscopies. The product showed better antiparkinsonian activity than the combination of levodopa and carbidopa.